Carl Schmitt and Justification of Science wars - Gedutis, Aldis (Sociologija. Mintis ir veiksmas, 2010)
From time to time in the fields of philosophy and sociology of science the political vocabulary is employed. Certain processes, which take place in science, are described using military notions such as “conflict”, “war”, “revolution” etc. This article concentrates on question, whether the vocabulary and instruments of political theories could enable more adequate understanding of the scientific processes that are socially influenced? In order to answer the latter question, Carl Schmitt’s political theory (concept of the political, friend-enemy distinction, notions of war and exception) is employed. The main objective of this article is to figure out possible benefits of the Schmitt’s ideas for current discussions in the field of philosophy of social sciences and humanities.
Keywords: Carl Schmitt; concept of the political; friend-enemy distinction; Alan Sokal; Science Wars; philosophy and methodology of social sciences and humanities